Pengetahuan Sikap dan Tindakan Masyarakat di Kelurahan Antang Kec.Manggala RW VI Tentang Penyakit Demam Berdarah Dengue (DBD) Kota Makassar Tahun 2015 - Azzahra, Sri Ayu; Bujawati, Emmi; Mallapiang, Fatmawaty (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Dengue Hemoragic Fever (DHF) is a infection disease that caused by dengue virus transmitted through mosquite bite aedes aegypty, as know together (DHF) is still the infections diseases potential outbreak. The purpose of this study to determine knowledge attitudes and actions of people in the village Antang RW VI Kec. find out knowledge attitude and community action in the pillars of the citizens (RW) VI in the the village of Makassar city districts Antang, type of research descriptive study with a random sample. The results showed enough knowledge of the category of 102 respondents’ (63%), whereas the category of positive attitude as much as 55 respondents’ (34%) , and less action category there were 107 respondents’ (98,1%) The research concloud respondents’ knowledge in the village Antang pillars of citizens (RW) VI is ‘’Enough’’ and the result can be consderaction for the helath agencies in order to survelance of dengue fever prevention practices and communities to be more concerned about the environment or do eradication advice mosquitoes (EMA). Key Words : Dengue Hemoragic Fever (DHF), Knowledge, Attitude And Measure